The Effect of Financial Leverage, Capital Turnover, Asset Composition, Firm Size on The Tendency of Financial Statement Fraud - Nina Fatimah; Agustin Fadjarenie (Politeknik Siber Cerdika Internasional, 2024)
This study aims to determine the factors that can predict the tendency of financial statement fraud in manufacturing companies. This study used a sample of 185 manufacturing companies that published financial reports on the Indonesia Stock Exchange for three years, namely 2019 to 2021. The data collection method was carried out by purposive sampling. While the analysis used was panel data regression. The results of the data analysis showed that all independent variables Financial Leverage (X1), Capital Turnover (X2), Asset Composition (X3), and Firm Size (X4) influenced the tendency of financial statement fraud.